POLITENESS IN BALINESE: THE APPEALING STRATEGIES - I Ketut Seken (ISSN)
The communicative behaviors of four klian adats were investigated to reveal their choice of politeness strategies that concern their intent to respect their interlocutors’ dignity. Designed as an ethnography of communication, the study used data collected mainly through participant and non-participant observations on the subjects’ communicative behaviors on various occasions of social interaction. Data analysis showed that various appealing strategies are used in the deliverance of acts with a potential to threaten the addressee’s face. The study is concluded with a claim that politeness strategies are related to the concept of face held by the community concerned. The appealing strategies are claimed to be the type of politeness strategies that feed to the addressee’s desires that his dignity be preserved and respected.